Mechanistic Studies of Idiosyncratic DILI: Clinical Implications - Uetrecht, Jack (Frontiers in Pharmacology, 2019)
The idiosyncratic nature of idiosyncratic drug-induced liver injury (IDILI) makes mechanistic studies very difficult, and little is know with certainty. However, the fact that the IDILI caused by some drugs is associated with specific HLA genotypes provides strong evidence that it is mediated by the adaptive immune system. This is also consistent with the histology and the general characteristics of IDILI. However, there are other mechanistic hypotheses. Various in vitro and in vivo systems have been used to test hypotheses. Two other hypotheses are mitochondrial injury and inhibition of the bile salt export pump. It is possible that these mechanisms are responsible for some cases of IDILI, or that these mechanisms are complementary and are involved in initiating an immune response. In general it is believed that the initiation of an immune response requires activation of antigen presenting cells by molecules such as danger-associated molecular pattern molecules (DAMPs). An attractive hypothesis for the mechanism by which DAMPs induce an immune response is through the activation of inflammasomes. The dominant immune response in the liver is immune tolerance, and it is only when immune tolerance fails that significant liver injury occurs. Consistent with this concept, an animal model was developed in which immune checkpoint inhibition unmasked the ability of drugs to cause liver injury. Although it appears that the liver damage is mediated by the adaptive immune system, an innate immune response is required for an adaptive immune response. The innate immune response is not dependent on specific HLA genes or T cell receptors and may occur in most patients and animals treated with a drug that can cause IDILI. Studies of the subclinical innate immune response to drugs may provide important mechanistic clues and provide a method to screen drugs for their potential to cause IDILI.